Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4103/0973-1075.285693
|View full text |Cite
|
Sign up to set email alerts
|

Indian society for study of pain, cancer pain special interest group guidelines on pharmacological management of cancer pain (Part II)

Abstract: The Indian Society for Study of Pain (ISSP), Cancer Pain Special Interest Group (SIG) guidelines on pharmacological management of cancer pain in adults provide a structured, stepwise approach, which will help to improve the management of cancer pain and to provide the patients with a minimally acceptable quality of life. The guidelines have been developed based on the available literature and evidence, to suit the needs, patient population, and situations in India. A questionnaire, based on the key elements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This systematic review evaluated fourteen cancer pain guidelines from various governmental and international scientific societies for quality assessment. [ 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ] Although the clarity of the presentation and scope and purpose domains was excellent in most guidelines, the real distinction was the domain of ‘rigour of development’. [ 40 41 ] The domain of applicability provided a practical insight into implementing a guideline to global clinical practice and was the highest in the WHO and NCEC-NCG guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review evaluated fourteen cancer pain guidelines from various governmental and international scientific societies for quality assessment. [ 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ] Although the clarity of the presentation and scope and purpose domains was excellent in most guidelines, the real distinction was the domain of ‘rigour of development’. [ 40 41 ] The domain of applicability provided a practical insight into implementing a guideline to global clinical practice and was the highest in the WHO and NCEC-NCG guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized RCT trial showed significant impairment of cancer pain by low-dose morphine compared with weak opioids, with similar tolerability and an earlier effect, suggesting low-dose morphine can be used [90,92]. This forwards the therapy option towards Step 3 and to date, the first choice to treat moderate to severe pain with strong opioids remains morphine [90,93]. MOP receptor drugs have shown superior analgesic efficacy and have been used for centuries as they seem to be the most potent analgesics [94].…”
Section: Analgesics: Nsaids and Opioidsmentioning
confidence: 99%
“…Professional oncology organizations have created pain management guidelines (PMG) to help health care providers effectively manage pain [25][26][27][28][29]. Unfortunately, adherence to PMG remains low [30][31][32][33], and understanding contextual barriers to low adherence of PMG is limited, especially in LMICs [32,34].…”
Section: Introductionmentioning
confidence: 99%